2017
DOI: 10.1002/jmv.24849
|View full text |Cite
|
Sign up to set email alerts
|

Down regulation of TRIF, TLR3, and MAVS in HCV infected liver correlates with the outcome of infection

Abstract: In virus-infected cells, pattern recognition receptors (PRRs) recruits their specific adaptor molecules, mitochondrial antiviral signaling protein (MAVS), TIR-domain-containing adapter-inducing interferon-β (TRIF), and TNF receptor associated factor (TRAF6) which induces interferon. Toll-like receptor 3 (TLR3) induces activation of the NF-kappa B (NF-κB) for interferon production. The study has been designed to assess the correlation of TLR3, MAVS, TRIF, and TRAF6 outcome of HCV infection. The 46 chronic hepat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 36 publications
3
8
0
Order By: Relevance
“…In human hepatocyte cultures [34,35] HCV infection triggered cleavage of MAVS and TRIF host proteins by HCV NS3/4A protease, disrupting TLR3-antiviral signaling. Reduction of protein levels of MAVS and TRIF was also observed previously in chronic HCV-infected livers [36,37]. Nevertheless, we observed a robust response to TLR3 signaling in the HCV-infected liver, which supports the idea that ISG induction is weak in HCV infected cells, but strong in HCV infected liver due to paracrine activation of NPC.…”
Section: Discussionsupporting
confidence: 91%
“…In human hepatocyte cultures [34,35] HCV infection triggered cleavage of MAVS and TRIF host proteins by HCV NS3/4A protease, disrupting TLR3-antiviral signaling. Reduction of protein levels of MAVS and TRIF was also observed previously in chronic HCV-infected livers [36,37]. Nevertheless, we observed a robust response to TLR3 signaling in the HCV-infected liver, which supports the idea that ISG induction is weak in HCV infected cells, but strong in HCV infected liver due to paracrine activation of NPC.…”
Section: Discussionsupporting
confidence: 91%
“…Hepatitis C virus (HCV) inhibits activation of NF-κB and IRF3 by proteolysis of TRIF (the adaptor protein, which links TLR3 and kinase). HCV utilizes the viral NS3/4A to cleave TRIF, which is an intermediate in TLR3, mitochondrial antiviral-signaling protein (MAVS), and RIG-I signaling pathways, therefore, dsRNA cannot induce the IFN production through these pathways [ 84 , 85 , 86 ]. Recently, an Orf virus (ORFV) virion-associated protein, ORFV119, was identified that inhibits the NF-κB signaling very early in infection [ 87 ].…”
Section: Intracellular Immune Ecosystem Of Virus-infected Cellsmentioning
confidence: 99%
“…Of note, TLR3 exhibits lower levels of expression in HCC when compared with adjacent tissues, and is positively associated with TRIF, nuclear factor-κB and IFN regulatory factor 3, which may inhibit HCC proliferation and promote HCC cell apoptosis (36). The expression levels of TLR3, TRIF and mitochondrial antiviral-signaling proteins were consistently decreased in chronic HCV-infected liver tissue, compared to that of than non-diseased liver tissue (37). Additionally, endogenous miR-155 can negatively regulate TLR3 expression and inhibit IFN-β production (38).…”
Section: Discussionmentioning
confidence: 99%